How we managed elective, urgent, and emergency orthopedic surgery during the COVID-19 pandemic. (May 2020) - Giorgi, P. D.; Gallazzi, E.; Capitani, P.; D'Aliberti, G. A.; Bove, F.; Chiara, O.; Peretti, G.; Schirò, G. R.
No abstract available